Mg-based Nanocomposites for hydrogen storage containing La23Nd8.5Ti1.1Ni33.9Co32.9Al0.65 alloys as additives. (2019) - Meena, Priyanka; Meena, Anoj; Jangir, Mukesh; Sharma, V.K.; Jain, I.P
Abstract: Mg based nanocomposites containing different concentrations of La23 Nd8.5 Ti1.1 Ni33.9 Co32.9 Al0.65 alloy has been undertaken at present work. Doped alloy was prepared by arc melting furnace and ball milled to get its nano structured. Hydrogen sorption properties of MgH2 + x wt% (x=10, 25 and 50) La23 Nd8.5 Ti1.1 Ni33.9 Co32.9 Al0.65 alloy was characterized for their thermal, morphological and structural properties. Result shows that the alloy significantly reduced onset temperature of desorption. The TGA analysis showed higher desorption temperature for milled MgH2 compared to x wt% alloy added MgH2 . Furthermore, the estimated activation energy for hydrogen desorption was found to be -177.90, -204.65, -79.15 and -185.29 kJ/mol for milled, 10 wt%, 25 wt% and 50 wt % MgH2 respectively and also shows the reduction of activation energy by 98 kJ/mol due to the addition of 25 wt% alloy additives resulted the improved hydrogen storage capacity. The phase and purity of MgH2 during milling was studied by XRD and it is revealed that maximum stable and improved phase alteration for Hydrogen sorption was obtained during 25 wt % alloy milling. Morphological studies by SEM were undertaken to investigate the effect of hydrogenation of nanostructured alloy. DSC investigations were carried out to investigate the effect of alloy on hydrogen absorption behaviour of MgH2 .